Skin/core fracture toughness of sandwich structures: a comparison of different experimental arrangements - Amal Alliyankal Vijayakumar; Muhammad Zahid; Stefano G. Corvaglia; Alfonso Maffezzoli (Polymer Testing)
Thermoplastic sandwich structures are most prominently used due to their intrinsic strength-to-weight ratio, recyclability, damping capabilities, and ease of processing. Nonetheless, skin/core debonding is a critical failure mode, limiting the stress transfer between the skin and core. This research adopts a cost-effective thermoforming approach for simultaneous commingled E-glass/Polypropylene (PP) fabric consolidation and closed-cell PP foam core bonding via a one-stage non-isothermal process. Several test methods have been developed to optimise and evaluate the interfacial bonding, analysing Mode I fracture energy. This study introduces a novel comparative evaluation of different variants of single cantilever beam (SCB) arrangements for measuring the Mode I interfacial fracture toughness of a single polymer (PP) sandwich structure, adopting a fixed and a horizontal sliding constraint for the sandwich panel. A rigid base with a flexible rod for load application was also used. Additionally, the study analyses the effects of skin thickness on testing arrangements and fracture toughness. The SCB with a sliding constraint is considered the most suitable configuration for measuring the Mode I-dominant fracture toughness of sandwich structures with varying skin thicknesses. However, the flexible long-loading rod and roller base configurations yield similar fracture toughness values for sandwich structures with thicker skins. The predominant mix Mode crack propagation at the crack tip limited the applicability of SCB with a rigid base in evaluating the pure Mode I. The skin thickness significantly affects the fracture toughness and debonding paths in sandwich structures. Throughout all Mode I arrangements and skin thicknesses, the crack advanced through densified or undeformed foam cells, indicating skin/core fusion bonding via the one-stage process.